Suppression of 8-oxoguanine DNA glycosylase (OGG1) activity produced positive impacts on disease severity, survival, and histopathological features of mice infected with Plasmodium berghei - Lawal, Mukhtar Gambo; Samaila, Abdullahi; Basir, Rusliza; Abd Aziz, Nur Aimi Liyana; Abdullah Alarabei, Abdusalam; Abdullah, Maizaton Atmadini; Abd Majid, Roslaini; Nordin, Norshariza; Hussain, Mohd Khairi; Ismail, Elysha Nur (Academic Press, 2025)
Malaria is a life-threatening disease, leading to significant morbidity and mortality. Malaria treatment remains a challenge due to its intricate pathophysiology and high levels of parasite resistance to many currently available antimalarial agents. Thus, there is an urgent need for more therapeutic strategies to combat the disease. OGG1 activity has been implicated in many inflammatory disease conditions, making suppressing OGG1 activity a potential target for therapeutic purposes. The current study aimed to determine the effect of suppressing OGG1 activity on the severity, survival, and histopathological features of P. berghei-infected mice. In this study, the effects of modulating OGG1 activity on parasitaemia development, disease progression, survival rate, and histopathological outcomes in major organs of Plasmodium berghei (P. berghei) infected mice were evaluated. A significant difference in the mean parasitaemia was observed between the Vehicle, TH5487-treated, and O8-treated mice (p < 0.001). Vehicle-treated mice exhibited markedly elevated mean percentage parasitaemia and succumbed to the infection earlier than TH5487 and O8-treated mice. The O8-treated mice showed the highest parasitaemia reduction of 39.60 ± 1.53 % compared to TH5487-treated mice. Histopathological examination revealed less severe pathological features associated with P. berghei infection in mice treated with OGG1 inhibitors than in vehicle-treated malaria mice. Significant differences were observed in the sequestration of PRBC, inflammation, hemozoin deposition, and architectural loss in mice treated with O8 and TH5487 compared to untreated malaria mice. The results of this study suggested that OGG1 suppression led to a decrease in parasitaemia and severity of the histopathological features in P. berghei-infected mice. The increased survival of treated malaria mice further supported this effect. These findings indicate that OGG1 suppression could be a potential therapeutic strategy during malaria.